A discrete population of IFN λ‐expressing BDCA3hi dendritic cells is present in human thymus. Issue 7 (10th March 2015) - Martínez, Víctor G; Canseco, Noelia M; Hidalgo, Laura; Valencia, Jaris; Entrena, Ana; Fernández‐Sevilla, Lidia M; Hernández‐López, Carmen; Sacedón, Rosa; Vicente, Angeles; Varas, Alberto
Abstract : Human thymus contains two major subpopulations of dendritic cells (DCs), conventional DCs (cDCs) and plasmacytoid DCs (pDCs), which are mainly involved in central tolerance and also in protecting the thymus against infections. In blood and peripheral organs cDCs include the subpopulation of BDCA3 hi DCs, considered as equivalents to mouse CD8α + DCs. In this study we describe in human thymus the presence of a discrete population of BDCA3 hi DCs that, like their peripheral counterparts, express CD13, low‐intermediate levels of CD11c, CLEC9A, high levels of XCR1, IRF8 and TLR3, and mostly lack the expression of CD11b, CD14 and TLR7. Thymic BDCA3 hi DCs display immature features with a low expression of costimulatory molecules and HLA‐DR, and a low allostimulatory capacity. Also, BDCA3 hi DCs exhibit a strong response to TLR3 stimulation, producing high levels of interferon (IFN)‐λ1 and CXCL10, which indicates that, similarly to thymic pDCs, BDCA3 hi DCs can have an important role in thymus protection against viral infections.